The Implementation Of Apriori Algorithm And Chi-Square Test In Determining Pattern Of Relationship Among The Rawi Hadis - Rahmadi Yotenka (EKSAKTA: Journal of Sciences and Data Analysis, 2017)
In this research apriori algorithm was implemented on rawi data of hadits to find out pattern of relationship among the rawi hadits in shahih bukhori book. The analogy that can be compared is by assuming that series or chain of rawi in every sanad of hadis may be regarded as transaction, while rawi hadis were items in transaction. Data mining is the method that was used to analyze with association rule technique. Association rule technique is used to find a pattern rule between a combination of items. To find out association rule by using association rule application, it is used apriori algorithm by observing three important measurement, namely support, confidence, and lift values. The analysis result of apriori algorithm showed that for minimum support 0.03 and minimum confidence 0.9 having 9 strong association pattern based on the sequence of rawi hadis of its sanad. Every rule of association which was strong, then tested by chi-square to prove that the rawis that were in the rule were truly connected or statisticly significance